Nicotine dependence versus smoking prevalence: comparisons among countries and categories of smokers. Issue 1 (1996) - Fagerström, K O; Kunze, M; Schoberberger, R; Breslau, N; Hughes, J R; Hurt, R D; Puska, P; Ramström, L; Zatoński, W
Abstract : OBJECTIVES: To collect available international data on nicotine dependence as defined by the Fagerström Test of Nicotine Dependence, and to compare levels of dependence among countries and categories of smokers. DATA SOURCES: Published and unpublished studies known to the authors and a search of EMBASE from 1985-1995. STUDY SELECTION: Studies included were those based on a nationally representative sample of a country's population, or a sample of smokers seeking cessation assistance. DATA SYNTHESIS: Smokers who seek help in stopping smoking are much more dependent than the average smoker. Men consistently score higher on dependence than women. Ex-smokers appear to have lower dependence than current smokers. A country with low smoking prevalence, the United States, seems to have smokers with higher dependence scores than countries where smoking is more prevalent (such as Austria and Poland). CONCLUSIONS: Successful tobacco control may result in a higher dependence among the remaining smokers (due to selective quitting by low-dependent smokers). The remaining highly dependent smokers may need more intensive treatment.